The Kasyf Method In The Narration Of Hadith From A Shi'a Perspective - Hikmah, Siti Fatihatul; Muhid, Muhid (El-Ghiroh : Jurnal Studi Keislaman, 2025)
Hadith, as the second source of Islamic law after the Qur'an, plays an important role in the formation of religious law and science. In the Islamic tradition, hadith narration uses various methods, one of which is the kashf method. This method is a typical approach in the Shi'a tradition that emphasizes the spiritual aspect and the authority of the Ahlul Bayt in understanding and narrating hadith. Unlike the Sunni tradition that prioritizes systematic verification of the sanad and matn, the kashf method functions as a means of revealing the inner meaning of the hadith that cannot always be reached by the textual approach. This study aims to analyze the kashf method in hadith narration from the Shi'a perspective and its implications in Islamic studies. Using a qualitative method based on literature study, this research compares the epistemological and methodological aspects between the kashf method and the conventional hadith narration approach. The results show that the kashf method functions not only as an intellectual approach but also as a spiritual process that emphasizes closeness to the Imam and the Ahlul Bayt in uncovering the inner meaning of the hadith. As such, it not only enriches the study of hadith in Islam but also strengthens the theological and philosophical foundations of the Shi'a scholarly tradition.